Cat o'nine tales - Archer, Jeffrey (London : Pan Books, 2007)
The man who robbed his own post office -- Maestro -- Don't drink the water -- It can't be October already -- The red king -- The wisdom of Solomon -- Know what I mean? -- Charity begins at home -- The alibi -- A Greek tragedy -- The Commissioner -- In the eye of the beholder.
Keywords: Fraud -- Fiction